Hearing Outcomes for an Underwater Endoscopic Technique for Transmastoid Repair of Superior Semicircular Canal Dehiscence. Issue 10 (December 2021) - Creighton, Francis X.; Zhang, Lisa; Ward, Bryan; Carey, John P.
Abstract : Objectives: To compare hearing outcomes between traditional microsurgical transmastoid repairs and underwater, endoscopic transmastoid repairs of superior semicircular canal dehiscence syndrome (SCDS). Methods: A retrospective review of 14 patients undergoing transmastoid repair of SCDS between 2013 and 2017. Preoperative, immediate (7–10 d) postoperative, and long-term (>6 wk) postoperative speech discrimination scores, pure-tone averages, as well as pure-tone air conduction and bone conduction thresholds were obtained at 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, 4000 Hz, and 8000 Hz. Hearing threshold changes were all calculated as preoperative thresholds subtracted from postoperative threshold at each frequency. Wilcoxon rank-sum tests were conducted to assess changes in postoperative hearing thresholds at both the immediate and long-term postoperative period between those undergoing the traditional transmastoid technique and the underwater, endoscopic transmastoid technique. Results: Our results demonstrate patients who underwent underwater transmastoid repairs had significantly less increase in their high-frequency bone conduction thresholds at both time periods, indicating less sensorineural hearing loss, compared to the traditional microscopic repair ( p = 0.02 [effect size, r = 0.4], p = 0.006 [ r = 0.6]). At long-term follow-up, there was also significantly improved pure-tone averages in the patients in the underwater repair cohort compared to the traditional group ( p = 0.004 [ r = 0.6]). There were no differences in air-bone gaps at any frequency or any time period between the two cohorts. Conclusions: Preliminary findings show that the underwater endoscopic technique may prevent sensorineural hearing loss during transmastoid repair of SCDS.